The effect of epitope‐based ligation of ICAM‐1 on survival and retransplantation of pig islets in nonhuman primates. (12th November 2017) - Lee, Jae‐Il; Kim, Jiyeon; Choi, Yun‐Jung; Park, Hi‐Jung; Park, Hye‐Jin; Wi, Hae Joo; Yoon, Sunok; Shin, Jun‐Seop; Park, Jin Kyun; Jung, Kyeong Cheon; Lee, Eun Bong; Kang, Hee Jung; et al.
Abstract: Background: Pig islet xenotransplantation is a promising alternative to allogeneic transplantation. However, the wide immunologic barrier between pigs and primates limits the long‐term survival of the graft. MD‐3, a novel monoclonal antibody (mAb) that recognizes a particular epitope of human ICAM‐1, can render T cells tolerant to a xenograft by arresting dendritic cell maturation. We report the long‐term survival of adult wild‐type pig islets and successful retransplantation in nonhuman primates using a protocol comprising induction with MD‐3 mAb and maintenance with anti‐CD154 mAb and sirolimus. Methods: Eleven rhesus monkeys were assigned to three groups. Group 1 (n = 4) involved treatment with MD‐3 induction, short‐term (<4 months) administration of anti‐CD154 mAb, and maintenance therapy with sirolimus. Group 2 (n = 4) involved treatment with MD‐3 induction and long‐term maintenance therapy with anti‐CD154 mAb and sirolimus. Group 3 (n = 3) involved only maintenance therapy with anti‐CD154 mAb and sirolimus. Diabetes was induced in monkeys by streptozotocin, and pig islets (61 000‐112 000 IEQ/kg for each transplant; up to 280 000 IEQ/kg per recipient) were infused through the portal vein. The in vivo functional potency of the isolated islets was tested by minimal model transplant in streptozotocin‐induced diabetic NOD/SCID mice, and the mean AUC of blood glucose level divided by the number of follow‐up days was calculated. Results: The islet grafts survived more than 6 months (between 225 and 727 days) in nine of 12 transplants of MD‐3‐treated groups 1 and 2, whereas in the absence of MD‐3 mAb, survival was <40 days. In three transplants of the MD‐3‐treated Group 2, functional graft survival was only for 104, 125, and 154 days. In these cases, a retrospective analysis suggested that the relatively short survival duration was associated with the relatively high AUC value in the NOD/SCID bioassay. Notably, when retransplantation was performed in Group 3, blood glucose control was extended up to 956 days, which was supported by MD‐3 mAb‐based suppression of adaptive immunity. No replication of cytomegalovirus genes was observed. Conclusions: Long‐term survival of pig islet xenografts and successful retransplantation were achieved with MD‐3 mAb‐based immunosuppression regimen in this pig‐to‐monkey transplantation model. It should be emphasized that these encouraging results were achieved following the transplantation of islets from pigs that had not been genetically modified. Considering that it is possible to further substantially reduce the destruction of grafted islet using genetically modified pig islet, the islet requirement could be reduced and much longer graft survival can be achieved.